Structural and functional changes of bioactive proteins in donor human milk treated by vat-pasteurization, retort sterilization, ultra-high-temperature sterilization, freeze-thawing and homogenization - Liang, Ningjian; Koh, Jeewon; Kim, Bum Jin; Ozturk, Gulustan; Barile, Daniela; Dallas, David C. (Frontiers in Nutrition, 2022)
Background: Donor human milk should be processed to guarantee microbiological safety prior to infant feeding, but this process can influence the structure and quantity of functional proteins. Objective: The aim of this study was to determine the effect of thawing, homogenization, vat-pasteurization (Vat-PT), retort sterilization (RTR) and ultra-high-temperature (UHT) processing on the structure of bioactive proteins in donor milk. Methods: Pooled donor milk was either not treated (Raw) or treated with an additional freeze-thaw cycle with and without homogenization, Vat-PT, RTR with and without homogenization, and UHT processing with and without homogenization. Overall protein retention was assessed via sodium-dodecyl sulfate (SDS-PAGE), and the immunoreactivity of thirteen bioactive proteins were assessed via enzyme-linked immunosorbent assay (ELISA). Results: Freeze-thawing, freeze-thawing plus homogenization and Vat-PT preserved all the immunoglobulins (sIgA/IgA, IgG, IgM) in donor milk, whereas RTR and UHT degraded almost all immunoglobulins. UHT did not alter osteopontin immunoreactivity, but Vat-PT and retort decreased it by ~50% and 70%, respectively. Freeze-thawing with homogenization, Vat-PT and UHT reduced lactoferrin’s immunoreactivity by 35%, 65% and 84%, respectively. Lysozyme survived unaltered throughout all processing conditions. In contrast, elastase immunoreactivity was decreased by all methods except freeze-thawing. Freeze-thawing, freeze-thawing plus homogenization and Vat-PT did not alter polymeric immunoglobulin receptor (PIGR) immunoreactivity, but RTR, RTR plus homogenization and UHT increased detection. All heat processing methods increased α-lactalbumin immunoreactivity. Vat-PT preserved all the growth factors (vascular/endothelial growth factor, and transforming growth factors β1 and β2), and UHT treatments preserved the majority of these factors. Conclusions: Different bioactive proteins have different sensitivity to the treatments tested. Overall, Vat-PT preserved more of the bioactive proteins compared with UHT or RTR. Therefore, human milk processors should consider the impact of processing methods on key bioactive proteins in human milk.